Attitudes and meanings regarding retirement: A comparative study according to gender in older adults - Hermida, Paula Daniela (2017)
The objective of the study is to assess whether the social expectations of «role» – differential of gender – influence in the adaptation of older adults to retirement, through meanings and attitudes toward retirement. An ex post facto design of simple retrospective character was used. It was attended by 300 self-governing middle class older adults; 150 men and 150 women residing in the Autonomous City, Buenos Aires, and influence areas (Argentina). We administered a questionnaire of sociodemographic data and retirement profile, a Scale of Attitudes toward retirement, and the argentine adaptation of the Meaning about retirement Questionnaire. The results show that women in comparison with men have more favorable attitudes toward retirement and they denote it more as «Rest», «Beginning» or «Continuity». This difference could be due to the differential impact that would result in the loss of the labor «role» according to gender.